Assessing Smart Growth Implementation and Its Impact on Urban Sprawl: A Content and GIS-Based Analysis - Krisnaputri, Nilam Atsirina; Pramitasari, Angrenggani; Sembiring, Elsa Try Julita; Aditantri, Rahmatyas; Rahmi, Lela Alifah; Prathivi, Maria Dini Gilang (Geoplanning: Journal of Geomatics and Planning, 2023)
Smart growth (SG) is a set of policies and regulations implemented to mitigate the expansion of urban sprawl. SG is a planning approach that prioritizes creating compact, mixed-use, and high-density urban areas to foster sustainable regional development. Nevertheless, it is important to note that both theoretically and practically SG is still undergoing refinement to ensure its suitability and applicability within the context of land control regulations in each location. The Bodetabek region in Indonesia is seeing rapid growth. Nevertheless, amidst this exponential expansion, the extent to which the local government has embraced SG concepts in its regional development remains uncertain. The primary aim of this study is to assess the extent to which SG concepts have been implemented in the domain of urban planning within the Bodetabek region. The methods of this paper are divided into several stages. Firstly, an examination is conducted to determine the extent to which SG concepts have been incorporated into the planning policy of the Bodetabek area. Subsequently, an assessment is made of the urban sprawl that has occurred in the Bodetabek area for 20 years. Lastly, an analysis is performed to investigate the pattern of urban expansion in the Bodetabek. The findings in this research show that the SG idea has been implemented in the Bodetabek region. The correlation between the proportion of SG content in Bodetabek local laws and land cover changes is evident. There is an inverse relationship between the proportion of SG content in local legislation and the extent of urban development in the Bodetabek area. Naturally, these findings provide preliminary evidence or indicators that can serve as a reminder of the potential of SG to curb urban sprawl, effectively aligning with established theoretical frameworks.